74 Polydioxanone Electrospun Filaments To Mimic Tendon Hierarchical Architecture. (5th September 2014) - Mouthuy, Pierre-Alexis; Zargar, Nasim; Hakimi, Osnat; Carr, Andrew
Abstract : Introduction: Nanofibrous electrospun materials have been previously proposed as scaffolds for tendon repair, for their ability to mimic tendon structures and to encourage tissue regeneration. 1, 2 In particular, creating filaments out of electrospun fibres offers the possibility to build larger structures with tailored morphologies and mechanical properties. In this paper, we present the potential of a new range of electrospun filaments which could be used for the repair of soft tissue such as tendon. Method: Continuous polydioxanone (PDO) electrospun filaments were produced with a single nozzle electrospinning set-up using a wire-guide collector. Filaments were stretched and assembled into 4- and 16-plied yarns by twisting them with a hand spinning device. Scanning electron microscopy was used to observe the morphology of the filaments and yarns. For in vitro work, human tendon cells were extracted from rotator cuff tendon tissue obtained during surgical repair, with appropriate ethical approval. Cells were cultured on the yarns for up to 21 days and morphology was observed by fluorescence microscopy (actin-phalloidin). For mechanical testing, 6 specimens per type of yarn were tested to failure in tension using Zwick machine at rate of 0.3 mm/min. Results: Stretching filaments resulted in alignment of the electrospun nanofibres along the fibre axis (Figure 1a ). The twist resulting from the assembly into 4-plied yarns is observed in Figure 1b . In vitro work shows excellent attachment of human tenocytes to the nanofibrous multifilament yarns (Figure 1c ). Moreover, cells are shown to align in the direction of the nanofibre orientation. As expected, the mechanical strength of the yarn is proportional to the number of filaments added (Figure 1d ). Discussions: While the bundles of aligned electrospun fibres closely resemble the morphology of collagen fibrils in native tendon, the assembly of the filaments into larger structures can be used to mimic tendons fascicles. In particular, native tendon fascicles have been shown to present a helix structure. 3 With their elongated shape, cells grown on these filaments also display a similar morphology to tenocytes seen in native tendons. Finally, adjusting the number of filaments can be used to tailor the mechanical strength of the yarn. With this combination of features, nanofibrous yarns hold great promises to support tendon repair. References: Hakimi O, et al . eCM Journal. 2012;24:344–357 Bosworth, et al . J Mater Sci Mater Med. 2013;24:1605–1614 Thorpe. et al . J R Soc . Interface. 2014;11:20131058